Nanocellulose dissolution in green solvents: Enhancing carrageenan biocomposites for sustainable hard capsule production - Okwuwa, Chigozie Charity; Fatmawati, Adam; Ries, Michael E. (Springer Netherlands, 2025)
This study investigates the dissolution of nanocellulose in a green choline chloride glycerol-based deep eutectic solvent (DES) to enhance the performance of carrageenan biocomposites for pharmaceutical applications. It is hypothesized that varying the hydrogen bond donor (HBD) ratio (glycerol) of the DES from 1:1 to 1:4 significantly enhanced the dissolution of nanocellulose, which is critical for improving the properties of the resulting biocomposite. Structural analyses showed that the optimal HBD ratio of the DES maximized nanocellulose dissolution, confirmed by X-ray Diffraction and Nuclear Magnetic Resonance spectroscopy, which demonstrated structural modifications and hydrogen bond breakdown. Thermal analysis indicated that the reinforced carrageenan biocomposite film and hard capsules exhibited enhanced thermal stability, with a higher degradation temperature of 245 °C and improved mechanical strength, as well as high tensile strength and capsule loop strength. It is suggested that the dissolution mechanism involves the disruption of hydrogen bonds in cellulose crystalline structure by the HBD in DES and promotes uniform integration within the carrageenan matrix. By tailoring DES composition to achieve dissolution and performance characteristics in industrial applications, this study offers a green and sustainable approach to enhance the functional properties of carrageenan biocomposites, advancing their potential use in environmentally friendly and high-performance pharmaceutical materials.